Health and Medicine In the Islamic Worldview (Study on Aqidah and Shari'ah Perspectives) - Lia Noviana; Asep Awaludin (Universitas Darussalam Gontor, 2022)
Muslims nowadays face at least two unfortunate realities in accordance with medicinal treatment. The first reality is to take any medicines available at pharmacies without any idea of the lawful-status of these medicines; halâl or harâm. Despite of the well-known brands and merits, there are quite serious contra-indications found within those medicines. The second reality is the Islamic -which are so called by alternative- medicines which, recently popular, yet mis-produced by some individuals to gain more profits. The outcome of this action made the price of these alternative medicines even higher. Thus, it is needed to find a solution that could overcome these conditions. That is the vision of reality and truth as a Muslim (Islamic worldview) toward healing as the problem solving. The characteristics of this Islamic worldview in accordance to this matter is the awareness as Muslim about the lawful status of medicines available, a consciousness as a producers of these medicines to help others based on Islamic spirit as well as to socialize ath-Thîb an-Nabawiy and finally the ultimate understanding that it is Allah SWT who gives health (asy-syifâ`)since He is ‘Asy-Syâfî’.